Frequency selective surface (FSS) for cellular signals shelding - Abdul Khalid, Nur khalida (2015)
This thesis proposes a frequency selective surface (FSS) for interference control causes by the proliferation of mobile devices. FSS is a periodic structure etched on a dielectric substrate which acts as a spatial filter. The proposed FSS is designed as a band-stop filter to attenuate the cellular signals operating at GSM900, GSM1800 and IMT2000 frequency bands. The employment of the FSS is an effective shielding technique as it eliminates the need for power supply and prevents the use of mobile phone without disrupting other types of communications. All the designs and simulations are done using the Computer Simulation Technology (CST) Microwave Studio software. There are three main groups of the FSS prototype designed in this study. The first group of the FSS prototype is etched on FR-4 substrate using the photolithography technique. On the other hand, the second group of the FSS prototype is printed on glossy paper substrate using the manual fabrication and inkjet printing techniques. These two techniques are implemented using the conductive silver pen and copper nanoparticle ink, respectively. The simulated results of the conventional square loop FSS printed on paper shows a good angular stability compared to the conventional square loop FSS printed on FR-4 substrate. The utilization of the inkjet printing technique is proposed in order to overcome the limitations of the manual fabrication technique. In order to transform a non-conductive printed pattern to a conductive one, the printed FSS element has to undergo the post-processing, called sintering. This consequently leads to a final prototype of the FSS printed on polyimide film. In order to validate the simulated results experimentally, the measurement is performed inside the anechoic chamber. The measured and simulated results are shown to be in a very good agreement with each other. FSS printed on glossy paper is highly recommended due to its very low cost and environmental-friendly material.